Predicting the grinding energy of vrm depending on material characterization. (1st September 2021) - Altun, Deniz; Benzer, Hakan; Gerold, Carsten; Schmitz, Christian
Highlights: Pilot scale vertical roller mill grinding tests and material characterization tests were performed. An energy-size reduction equation was derived to estimate the specific grinding energy of the vertical roller mill based on a laboratory characterization test. The model was applied to eight ores of varying resistance to compression grinding with acceptable results. The model is a function of f80, p80, ore index and feed size range. Abstract: This paper presents the studies carried out to estimate the grinding energy of vertical roller mills via breakage test. An extensive laboratory and pilot scale test work was performed. In the first step, breakage characteristics of eight samples having different competence were determined by piston-die tests. Then, the samples were subjected to a size reduction process using a pilot scale vertical roller mill. Feed size, product size and energy data from pilot scale grinding tests were evaluated with material characterization tests. Based on energy-size reduction models proposed in the literature, equations were derived to estimate the grinding energy of the vertical roller mill by using the size and piston-die test data.